Research on the development of the concept of death in children and its influencing factors - Jingjing, Liu; Fuyan, Liu (Frontiers in Psychology, 2024)
In this study, 114 Chinese children aged 5–6 years old in Henan Province and 114 mothers were selected as research subjects, 59 boys, 55 girls, and 114 mothers. Semi-structured interviews were conducted with children to test the development of the concept of death in children. At the same time, a questionnaire survey was conducted among the children’s mothers to analyze the influencing factors of the development of children’s concept of death. The results of the study showed that children aged 5–6 years had the concept of death, and the sub-components were acquired in a certain order, but the development was not balanced, the overall level of development of the concept of death is slightly higher in girls than in boys; “Whether or not the family talked openly about the topic of death” had a significant effect on the sub-component of the children’s concept of death, “Universality of death” (β = −0.301, t = −2.007, p < 0.05) and “causality of death” (β = 0.315, t = 2.582, p < 0.05); and “whether or not there was the experience of exposure to death-related events” had a significant effect on “Irreversibility of death” (β = −0.326, t = −2.36, p < 0.05); Mothers’ natural acceptance of death (β = −0.293, t = −2.209, p < 0.05) and convergence-orientated acceptance (β = 0.415, t = 2.315, p < 0.05) had significant effects on the “inorganicity of death” of children’s concept of death.